New categorization of chest pain: noncardiac is in, atypical is out! - Settelmeier, Stephan; Steven, Sebastian; Post, Felix; Ahrens, Ingo; Giannitsis, Evangelos; Breuckmann, Frank (Herz, 2024)
Chest pain poses a diagnostic challenge in the emergency department and requires a thorough clinical assessment. The traditional distinction between “atypical” and “typical” chest pain carries the risk of not addressing nonischemic clinical pictures. The newly conceived subdivision into cardiac, possibly cardiac, and (probably) noncardiac causes of the presenting symptom complex addresses a much more interdisciplinary approach to a symptom-oriented diagnostic algorithm. The diagnostic structures of the chest pain units in Germany do not currently reflect this. An adaptation should therefore be considered.
Gesehen am 27.02.2025